Análise da influência de planos de manejo florestal na conservação ambiental em áreas de projetos de assentamentos federais - Guedes, Simão Pedro Pinheiro de Andrade (2023)
The forest management plan in the Caatinga is an essential strategy to ensure the conservation of natural resources in this unique biome and promote the sustainable use of its resources. The plan involves the adoption of specific measures to protect biodiversity, control the exploitation of timber and other forest products, promote the restoration of degraded areas, and ensure the participation of local communities, in the case of this research, the agrarian reform settlers. Although the Caatinga is a predominantly arid biome, it possesses rich biodiversity and plays an important role in conserving natural resources and sustaining local communities. This research analyzed whether there is a difference in environmental conservation between the Legal Reserves of Settlement Projects with the activity of Sustainable Forest Management Plan and those without this activity, located in the Caatinga region of Russas - CE, where it is the largest ceramic pole in the state of Ceará. The environmental situation of 18 Settlement Projects was compared, with 09 having implemented the Forest Management Plan and 09 where there is no Forest Management Plan, using the Vegetation Indices: Normalized Difference Vegetation Index - NDVI and Soil-Adjusted Vegetation Index - SAVI. The temporal analysis was conducted for the dry periods of the years 2011 and 2020. It should be noted that in 2011, no Forest Management Plan was implemented. The analysis was carried out from the obtaining and processing of LANDSAT 5 and LANDSAT 8 orbital images, respectively. The Student's t-test, with a 5% level of significance, was found to be ideal for the statistical analysis in comparing the means of conserved area. The research showed a relationship between the Forest Management Plan and the preservation of the Legal Reserves. For the year 2011, there were no statistical differences between the means of conserved area. For the areas without the Forest Management Plan, it was shown that there was a decrease in the conserved area between the years 2011 and 2020, which did not happen with the Settlements that have the Forest Management Plan. The year 2020 showed that there was a statistical difference between the conserved areas in the legal reserve of the Settlements with and without the Forest Management Plan. Through the analysis of the vegetation indices, it was possible to identify degraded areas in the Legal Reserves. They proved to be useful in monitoring changes in plant cover over time. Comparing satellite images in the different periods, it was possible to identify areas where significant alterations occurred in the vegetation. The NDVI and SAVI were efficient in detecting deforestation in the Caatinga, with SAVI being more efficient for this purpose. The Forest Management Plan showed to have influence on the environmental conservation of the Legal Reserves. Therefore, it appears as another sustainable alternative for income generation in the semiarid region.